Planning of Fieldwork which is Suitable for Outcomes of Physical Geography in High-Schools Education (Istanbul Sample) - (:unkn) unknown (MARMARA UNIV, 2018)
This research aims to plan the fieldwork that are suitable to the outcomes in the geography-teaching program of high schools. In the end, by determining locations in Istanbul city on which fieldwork can be carried out that are suitable to these outcomes, an important practise gap will be filled up. Geographical information that are theoretically mentioned in a classroom environment will be transformed in to practise. In our research, document review which is one of the qualitative research methods was adopted. Observation was used as the data collection method. Data was analysed through sampling method. Planning the schedule of the fieldwork will be up to the teachers. That, where fieldwork suitable to outcomes within geography teaching programs will be carried out was not mentioned previously, this case constitutes the main problem. For which outcomes the fieldwork will be carried out is mentioned in the geography, teaching program. Next, by taking the Istanbul's geographical conditions in to account, samples were determined. Location information of the determined lands were identified in data land study fields were showed by photos taken before. Data collected revels that there are many locations suitable for carrying out geographical fieldwork.
Keywords: Geography Teaching; Fieldwork in Istanbul; Learning Outcomes